Pengembangan Ide Bisnis BUMDES dan UMKM di Desa Purworejo, Pesawaran, Lampung - Putri, Lidya Ayuni; Suningsih, Sri; Karim, Mirwan; Hendrawaty, Ernie (Jurnal Nusantara Mengabdi, 2023)
Purpose: To provide knowledge and advocate the Purworejo community for the importance of digital marketing and the availability of adequate facilities to implement it, helping to market their products online and develop their businesses to achieve maximum profit. Additionally, it aims to enable them to withstand market competition. Methodology: The focus group discussion (FGD) approach was used to conduct FGDs with business stakeholders in Purworejo village to discuss, exchange ideas, and formulate better business development steps. Training and Mentoring are also implemented for business stakeholders in BUMDES and SMEs to enhance managerial and marketing skills. Results: The research results indicate the success of educational activities in enhancing participants' knowledge and understanding of digital marketing and content. Although there is still room for improvement, this education has shown a positive impact on equipping participants with relevant skills and insights in the era of digital marketing and Industry 4.0 revolution. Limitations: The limitation of this service lies in the participants' infrastructure, in which each participant is not proficient in using digital tools. Furthermore, this service's limitation is only focused on the conventional-to-digital transition process and content creation, without delving deeper into monitoring the development of targeted Micro, Small, and Medium Enterprises (MSMEs) and Village-Owned Enterprises (BUMDes). The hope for the future is to continuously enhance and optimize this educational program to support the development of participants in facing the challenges of an increasingly digital and competitive business world. Contribution: This service is beneficial to the community, as it assists Micro, Small, and Medium Enterprises (UMKM) and Village-Owned Enterprises (BUMDes) in harnessing digital media in the region, unlocking its potential to enhance family income and boost the local economy.